D- VS L-methionine utilization by growing steers - Campbell, C.G.; St. Jean, G.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Increasing the amino acid supply to the small intestine of growing cattle can increase performance, if specific amino acids are limiting. Although this can be accomplished by feeding rumen undegradable protein, a more economical approach may be supplementing only those amino acids that actually limit performance, but in a form that will bypass the rumen. Methionine (MET) is thought to be a limiting amino acid for growing cattle. DL-MET, a 50 :50 mixture of natural methionine (L-MET) and the unnatural optical isomer (D-MET) is used widely in monogastric rations. Ruminally protected DL-methionine is also available for cattle; however, little information is available about its utilization by growing steers. We studied the efficiency of utilization of D- vs L-MET by growing steers by measuring nitrogen retention of steers postruminally supplemented with graded levels of D- or LMET. Nitrogen retention increased linearly in response to infusion of both L-MET and D-MET, with similar responses for the two isomers. The efficiency of utilization of DMET relative to L-MET was estimated to be 95.5%. In conclusion, D-MET was similar to L-MET in increasing nitrogen retention of growing steers.
Keywords: Beef; Methionine; Growing steers; Nitrogen retention